Analisis Margin Pemasaran dan Strategi Pemasran Kompetitif Agroindustri Tahu di Desa Jampes Kecamatan Pace Kabupaten Nganjuk (Agridevina : Berkala Ilmiah Agribisnis, 2022)
Agriculture is a source of raw materials for the agricultural product processing industry (agro-industry) such as tofu agro-industry. This study aims to improve marketing margins and competitive marketing strategies for Tofu Agroindustry in Jampes Village, Pace District, Nganjuk Regency. The research was conducted in 2022 with the survey location being the Tofu Agro-industry UMKM in Jampes Village, Pace District, Nganjuk Regency. The data is divided into primary data and secondary data. Primary data is obtained from interviews using structured data (questionnaire) on respondents represented by 2 UMKM Agroindustry Tofu owners. The analytical method used in this research is marketing margin analysis and SWOT analysis. The results of this study are that there are two marketing channels in Mr. Sumadi's UMKM Tofu, the first channel is from the producer directly to the end consumer. And channel II, namely from producers then distributed to retailers and resold to consumers. The longer the marketing channel, the lower the price offered to farmers. Based on market performance analysis, deep tofu marketing in that area is less efficient. This can be seen from the marketing margins on all major marketing channels, the distribution of margins is not evenly distributed, the share of prices received by farmers is still low, the ratio benefits and costs vary. DOI : https://doi.org/10.33005/agridevina.v11i2.3529